Hydrogels in Tissue Engineering - Esmaiel Jabbari (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Hydrogels are the foundation of regenerative medicine as a supportive matrix for cell immobilization and growth factor delivery. The fate of implanted cells is mediated by cell-matrix interaction at multiple scales and timed-release of growth factors to guide the differentiation and maturation of cells. Recently, there has been great interest in hydrogels with a hierarchical structure that mimics the complex interaction of cells with a microenvironment that can locally release growth factors to specific cells. Related topics in this Special Issue include hydrogels with a hierarchical structure; hybrid, degradable, and load-bearing hydrogels; hydrogels for cell encapsulation, micro-patterning, microfluidic devices, biofabrication, and high-throughput screening; and hydrogels that modulate the body's immune response.